Los medios de comunicación en el desarrollo cognitivo en los niños del 1er año paralelo “A” de la Unidad Educativa San Andrés Cantón Guano Provincia de Chimborazo período 2015 – 2016 - Avalos Fiallos, Patricia Maribel (2016)
This research work is descriptive, since it is a field research by contact with the scene, observing and describing the variables behavior of the problematic, without affecting in Unidad Educative “San Andrés”. The main objective is to determine the importance of the media and their impact on cognitive development in children of the first year, parallel "A" of the Unidad Educative San Andrés, Guano canton, Chimborazo province, period 2015-2016. For this, the existing problems were identified in the institution, necessary bibliography was consulted, the same that allowed obtaining data from different authors through books, texts, documents, internet, and others to broaden and deepen different approaches, theories and conceptualizations. The methods used were the analytic-synthetic, to analyze the problem; Inductive-deductive that through this method could analyze information from the data collected. Instruments such as the survey to teachers and checklist to children of first year of this institution were applied. It can be determined as conclusion that the use of the media is very important from consideration as curriculum and teaching materials, because it has become essential in an educational process to achieve cognitive development in children of first year. Moreover being the radio, television and magazines the mainstream media that teachers use as transcendental resource for the teaching-learning process to achieve cognitive development in the boys and girls of the Unidad Educative “San Andrés”. In addition, it was determined that the child is able to remember, to associate, organize, identify, describe, classify, and memorize objects according to their stage of development with the use of the media.